Anterior Segment Optical Coherence Tomography Angiography Following Trabecular Bypass Minimally Invasive Glaucoma Surgery - Gan, Jinyuan; Sng, Chelvin C. A.; Ke, Mengyuan; Chieh, Chew Shi; Tan, Bingyao; Schmetterer, Leopold; Ang, Marcus (Frontiers in Medicine, 2022)
Objective To assess anterior segment optical coherence tomography angiography (AS-OCTA) imaging of the episcleral vessels before and after trabecular bypass minimally invasive glaucoma surgery (MIGS). Design A prospective, clinical, single-centre, single-arm pilot feasibility study conducted at National University Hospital, Singapore. Subjects Patients with primary glaucomatous optic neuropathy undergoing Hydrus Microstent (Ivantis Inc., Irvine, CA, USA) implantation, who require at least one intra-ocular pressure-lowering medication. One or two eyes per patient may be enrolled. Methods We performed AS-OCTA (Nidek RS-3000 Advance 2, Gamagori, Japan) pre- and up to 6 months post-MIGS implantation using a standard protocol in all cornealimbal quadrants, to derive episcleral vessel densities (VD) using a previously described technique. Main Outcome Measures Episcleral VD pre- and post-surgery, in sectors with and without the implant. Results We obtained serial AS-OCTA images in 25 eyes undergoing MIGS implantation (23 subjects, mean age 70.3 ± 1.5, 61% female) with mean preoperative intraocular pressure (IOP) of 15.5 mmHg ± 4.0. We observed reductions in postoperative episcleral VD compared to preoperative VD at month 1 (mean difference −3.2, p = 0.001), month 3 (mean difference −2.94, p = 0.004) and month 6 (mean difference −2.19, p = 0.039) in sectors with implants (overall 6 month follow-up, p = 0.011). No significant changes were detected in episcleral VD in the sectors without implants (p = 0.910). Conclusion In our pilot study, AS-OCTA was able to detect changes in the episcleral VD following trabecular bypass MIGS, which may be a useful modality to evaluate surgical outcomes if validated in future studies.